Pengaruh Pendekatan I‑SETS (Islamic, Science, Environment, Technology, Society) Terhadap Hasil Belajar IPA Siswa Sekolah Dasar - Rima Nugrahani; Aufa, Minzani; Irham Nugroho (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2026)
This study aims to analyze the effect of implementing the I-SETS (Islamic-Science, Environment, Technology, Society) approach on science learning outcomes of third-grade students at MI Muhammadiyah Terpadu Harapan Kota Magelang. The study was motivated by low science achievement resulting from the dominance of conventional, teacher-centered instruction, in which 40% of students had not yet achieved the Minimum Learning Achievement Criteria. This research employed a quantitative experimental design involving an experimental class and a control class. Learning outcome data were collected through pre-test and post-test instruments and analyzed using Paired Sample t-test and Independent Sample t-test. The results revealed a highly significant improvement in learning outcomes in the experimental class after the implementation of the I-SETS approach, with an increase of 62.35% from pre-test to post-test. In contrast, the control class showed a relatively lower improvement of 35.23%. Furthermore, the Independent Sample t-test indicated that the post-test mean score of the experimental class was significantly higher than that of the control class (sig. 0.000 < 0.05). Therefore, it can be concluded that the I-SETS approach is effective and has a positive and significant impact on improving elementary students’ science learning outcomes.